Penggunaan Media Teknologi, Student Engagement, dan Kinerja Dalam Pembelajaran Akuntansi: Studi Kasus pada Accounting Software â€œAccurateâ€ - Se Tin - (Universitas Kristen Maranatha, 2012)
The purpose of this study is to research the relation about accounting software (Accurate)and student engagement and student performance. A number of 186 students in accounting class of Maranatha Christian University participated in this research and valid data is 128. Regression Linear and descriptive analysis are used in this research. The results show that the value of R-square is 0.993, it indicates that there is linear correlation between engagement and students’ score in practical accounting software (Accurate).